Eulalia! / 19. - Jacques, Brian (Jacques, Brian. Redwall series., 2007)
Lord Asheye of Salamandastron has a prophecy: a new Badger Lord must take his place and reign over the legendary badger fortress. Maude Maudie, a feisty haremaid of the Long Patrol, is just the one to track down this young warrior.